FAKTOR YANG MEMPENGARUHI PERILAKU GENERASI MILENIAL TERHADAP KEPUTUSAN MENGGUNAKAN APLIKASI GRABFOOD - Rosita, Rahmi (JURNAL LENTERA BISNIS, 2020)
The industrial revolution is marked by the use of new technologies in various fields. Along with the revolution and evolution in the industrial world throughout the world, marketing also experienced changes as a result of the adaptation and development of the industry. The purpose of this research is to find out how the behavior of millennial generation in using the Grabfood application. An approach method to study the research object by trying to explain the relationship between the research variables using descriptive analysis and multiple linear regression analysis test instruments. The results showed that the factors of consumptive behavior were the most influential and dominant factors in millennial generation in using the Grabfood application.Keyword: Millennial Generation, Application, Grabfood